Prospective comparison of subjective arousal during the pre-sleep period in primary sleep-onset insomnia and normal sleepers. - Robertson, J; Broomfield, N; Espie, C (2007)
Psychophysiological insomnia (PI) is the most common insomnia subtype, representing 12-15% of all sleep centre referrals. Diagnostic guidelines describe PI as an intrinsic sleep disorder involving both hyperarousal and learned sleep-preventing associations. Whilst evidence for the first component is reasonably compelling, evidence for learned (conditioned) sleep effects is markedly lacking. Indeed, to date no study has attempted to capture directly the conditioned arousal effect assumed to characterize the disorder. Accordingly, the present study explored variations in subjective arousal over time in 15 PI participants (sleep onset type) and 15 normal sleepers (NS). Self-report measures of cognitive arousal, somatic arousal and sleepiness were taken at three time points: 3 h before bedtime (early to mid-evening); 1 h before bedtime (late evening); and in the bedroom at lights out (bedtime) across four, 24-h cycles. Fluctuations in mean arousal and sleepiness values, and in day-to-day variation were examined using analyses of variance. Participants with PI were significantly more cognitive aroused and significantly less sleepy relative to NS, within the bedroom environment. These results support the tenet of conditioned mental arousal to the bedroom, although competing explanations cannot be ruled out. Results are discussed with reference to extant insomnia models.